Barriers to the construction of early childhood education as an educational space in rural communes (Polis (Santiago), 2018)
The following article presents the results of a study that investigated the barriers facing early childhood education because of the poor quality of pre-school centers, the family’s impairment to early childhood education, the problems caused by the lack of local management capacity, and the characteristics of rural communes in their construction as an educational space. The methodology of this research was quantitative and qualitative, and pre-schools and municipal actors related to early childhood education in rural communes of the region of Coquimbo and Maule, were investigated. The results showed the importance of family participation in achieving quality on pre schools, and also that municipalities are obstructionist in the exercise of leading preschools to success. Through this analysis we propose to consider a synergy that seems to be not approached enough in public policy: that is, the relationship between early childhood and education
Keywords: early childhood education; quality; families; local management; rural communes